2021
DOI: 10.1039/d1ra06146a
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis and functional studies of self-adjuvanting multicomponent anti-HER2 cancer vaccines

Abstract: Tricomponent anti-HER2 vaccine that synthesized by incorporating MFCH401 with Pam3CSK4 and helper T cell epitope could efficiently trigger anti-HER2 antibodies and induce specific recognition and killing to HER2-overexpressing breast cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Hence, this novel platform has several new aspects compared to the existing protein-based anti-METH vaccine platforms. One can further optimize antibody responses by using self-adjuvanting tricomponent vaccines that include antigen-glycoprotein-universal T helper epitope PADRE and Pam 3 CysSer adjuvant [51][52][53] or the use of nanoparticles [54][55][56]. Previous research on the efficacy and stability of relevant candidate MS vaccine using oxidized mannan conjugated with antigenic epitope peptide MOG35-55 is in line with and supports the findings of this study [57,58].…”
Section: Discussionsupporting
confidence: 86%
“…Hence, this novel platform has several new aspects compared to the existing protein-based anti-METH vaccine platforms. One can further optimize antibody responses by using self-adjuvanting tricomponent vaccines that include antigen-glycoprotein-universal T helper epitope PADRE and Pam 3 CysSer adjuvant [51][52][53] or the use of nanoparticles [54][55][56]. Previous research on the efficacy and stability of relevant candidate MS vaccine using oxidized mannan conjugated with antigenic epitope peptide MOG35-55 is in line with and supports the findings of this study [57,58].…”
Section: Discussionsupporting
confidence: 86%
“…MRI has many advantages, including that it is non-invasive, does not involve exposure to radiation, has high resolution, and can intuitively display the morphological and functional information of breast cancer, which will increase the accuracy of breast cancer diagnosis (14)(15)(16). Numerous studies (17)(18)(19)(20) have found that imaging groups can be used to predict the diagnosis, type, and lymph node metastasis of breast cancer. Breast MRI (21,22) has achieved satisfactory clinical results in this area.…”
Section: Discussionmentioning
confidence: 99%